The expression of peripheral blood inflammatory factors in patients with acute ischemic stroke and its correlation with patients’ prognosis: Inflammatory factors in peripheral blood of stroke patients - Han, Zhaodan; Hong, Congya; Lang, Yasong (Cellular and Molecular Biology, 2023)
This study aimed to determine the neutrophil/lymphocyte ratio (NLR) and platelet/lymphocyte ratio (PLR) in patients with acute ischemic stroke (AIS) and their correlation with the patients’ prognosis. For this purpose, a total of 100 patients with AIS admitted to the neurology department of our hospital between March 2019 and February 2022 were selected as the AIS group, and all patients were treated with recombinant tissue plasminogen activator (rtPA) intravenous thrombolysis. According to the Modified Rankin Scale (mRS) scores three months after thrombolysis, patients in the AIS group were grouped into a favourable group (mRS score: 0-2 points) and an unfavourable group (mRS score: 3-6 points). Additionally, 100 healthy individuals who received physical examination over the same time span were enrolled into a health group. The NLR and PLR of each group were compared, and receiver operating characteristic (ROC) curves were drawn to analyze the predictive value of separate tests of NLR and PLR and joint tests of them for unfavourable prognosis of AIS patients who received thrombolytic therapy. Logistic regression analysis was conducted to understand the influencing factors of unfavourable prognosis of the AIS patients who received thrombolytic therapy. The results indicated that the AIS group exhibited significantly higher NLR and PLR levels compared to the health group. The unfavourable group showed notably higher NLR and PLR than the favourable group. Lymphocytes, NLR and PLR were independent risk factors for predicting the prognosis of AIS patients who received thrombolytic therapy. Additionally, NLR and PLR had high diagnostic efficiency in predicting patients' adverse prognoses, and the diagnostic efficiency of their combination is higher than that of single detection. In conclusion, NLR and PLR have certain predictive values for the prognosis of AIS patients who received thrombolytic therapy, and they can serve as indicators for disease monitoring and prognosis evaluation of AIS patients.